KETERAMPILAN STUDI TENTANG PENERAPAN RAGAM HIAS FLORA MENGGUNAKAN TEKNIK KOLASE DENGAN MEDIA KERTAS ORIGAMI - Vriti Alya Vithaloka; Nelson Tarigan (Universitas Negeri Medan, 2022)
This study aims to determine the process of applying ornamental flora using collage technique using origami paper media for students of SMP Muhammadiyah 1 Medan and also to find out the results of applying decorative collage techniques using origami paper media for students at SMP Muhammadiyah 1 Medan. This study applies a collage technique using origami paper materials, especially in decorative materials. The population of this study were all seventh grade students of SMP Muhammadiyah 1 Medan, totaling 170 students, and a sample of 30 students with collage decorative works determined by the cluster sampling technique (Area Sampling). The indicators for the assessment of the work are the ability to produce attractive colors, neatness and also the composition of the collage decorative works. Data collection techniques used literature study, observation, documentation and interviews. The data analysis technique used descriptive qualitative. The results of this study indicate that the quality of the results achieved by students in the good category with an average value of 74.99.